2023
DOI: 10.1097/ftd.0000000000001078
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Machine Learning Approaches to Facilitate Therapeutic Drug Management and Model-Informed Precision Dosing

Abstract: Background:Therapeutic drug monitoring (TDM) and model-informed precision dosing (MIPD) have greatly benefitted from computational and mathematical advances over the past 60 years. Furthermore, the use of artificial intelligence (AI) and machine learning (ML) approaches for supporting clinical research and support is increasing. However, AI and ML applications for precision dosing have been evaluated only recently. Given the capability of ML to handle multidimensional data, such as from electronic health recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…[17][18][19][20] Recent studies have suggested that using artificial intelligence in tandem with pharmacometric approaches can improve patient outcomes. 21 Indeed, machine learning methodologies can process high dimensional data and have demonstrated good performance in predicting treatment outcomes, including antidepressant response. [22][23][24] Yet, no one has evaluated a machine learning approach leveraging pharmacokinetic data to predict antidepressant-related side effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] Recent studies have suggested that using artificial intelligence in tandem with pharmacometric approaches can improve patient outcomes. 21 Indeed, machine learning methodologies can process high dimensional data and have demonstrated good performance in predicting treatment outcomes, including antidepressant response. [22][23][24] Yet, no one has evaluated a machine learning approach leveraging pharmacokinetic data to predict antidepressant-related side effects.…”
mentioning
confidence: 99%
“…For instance, therapeutic drug monitoring and model‐informed precision dosing can help optimize dosing to balance the efficacy‐tolerability tradeoff, and these strategies could benefit SSRI‐treated patients 17–20 . Recent studies have suggested that using artificial intelligence in tandem with pharmacometric approaches can improve patient outcomes 21 . Indeed, machine learning methodologies can process high dimensional data and have demonstrated good performance in predicting treatment outcomes, including antidepressant response 22–24 .…”
mentioning
confidence: 99%
“…4,5 Recently, hybrid approaches integrating AI/ML with mathematical modeling and simulations have been proposed and gained great momentum in the pharmacometric landscape to solve different tasks [6][7][8][9][10] such as pharmacokinetic (PK) and pharmacodynamic (PD) predictions, 6,7 covariate selection 6,7,10,11 as well as treatment optimization, especially in a precision dosing context. 12 Precision dosing refers to tailoring the dose on each individual patient at each given time, in order to ensure the greatest benefits and least risks. It is recommended for classes of compounds characterized by a narrow therapeutic index and/or high interindividual variability (IIV).…”
Section: Reinforcement Learning and Pk-pd Models Integration To Perso...mentioning
confidence: 99%
“…AI/ML are now present throughout the entire continuum of pharmacology research, from the early drug discovery phases 1–3 to the clinical practise 4,5 . Recently, hybrid approaches integrating AI/ML with mathematical modeling and simulations have been proposed and gained great momentum in the pharmacometric landscape to solve different tasks 6–10 such as pharmacokinetic (PK) and pharmacodynamic (PD) predictions, 6,7 covariate selection 6,7,10,11 as well as treatment optimization, especially in a precision dosing context 12 …”
mentioning
confidence: 99%
“…Similar approaches have shown improvements in isavuconazole exposure prediction 76 . Therapeutic drug management and model‐informed precision dosing have been covered elsewhere 77 …”
Section: How Can Ai Be Used In Clinical Pharmacology?mentioning
confidence: 99%